Pristolepis rubripinnis, a new species of fish from southern India (Teleostei: Percomorpha: Pristolepididae) - Britz, Ralf; Kumar, Krishna; Baby, Fibin (Zootaxa, 2012)
Pristolepis rubripinnis, new species, from the Pamba and Chalakudy rivers in Kerala, India, is distinguished from all otherspecies of the genus by its colour pattern, which includes orange-red soft dorsal, soft anal and caudal fins, and a yellow toorange pelvic fin. It differs further from its southern Indian congener P. marginata in having 4 or 5 scales above the lateral line (vs. 3) and 10 scales below it (vs. 9)